Insight and emotion regulation in schizophrenia: A brain activation and functional connectivity study - Larabi, Daouia I. (Neuroimage Clin, 2018)
BACKGROUND: Insight is impaired in the majority of schizophrenia patients. The exact neural correlates of impaired insight remain unclear. We assume that the ability to regulate emotions contributes to having good clinical insight, as patients should be able to regulate their emotional state in such a way that they can adapt adequately in order to cope with impaired functioning and negative stigma associated with a diagnosis of schizophrenia. Numerous studies have shown emotional dysregulation in schizophrenia. We investigated the association between insight and brain activation and connectivity during emotion regulation. METHODS: Brain activation during emotion regulation was measured with functional MRI in 30 individuals with schizophrenia. Two emotion regulation strategies were examined: cognitive reappraisal and expressive suppression. Clinical insight was measured with the Schedule for the Assessment of Insight – Expanded, and cognitive insight was measured with the Beck Cognitive Insight Scale. Whole brain random effects multiple regression analyses were conducted to assess the relation between brain activation during emotion regulation and insight. Generalized psychophysiological interaction (gPPI) was used to investigate the relation between task-related connectivity and insight. RESULTS: No significant associations were found between insight and neural correlates of cognitive reappraisal. For clinical insight and suppression, significant positive associations were found between symptom relabeling and activation in the left striatum, thalamus and insula, right insula and caudate, right pre- and postcentral gyrus, left superior occipital gyrus and cuneus and right middle and superior occipital gyrus and cuneus. Furthermore, reduced clinical insight was associated with more connectivity between midline medial frontal gyrus and right middle occipital gyrus. For cognitive insight and suppression, significant positive associations were found between self-reflectiveness and activation in pre- and postcentral gyrus and left middle cingulate gyrus. CONCLUSIONS: Our results suggest an association between the capacity to relabel symptoms and activation of brain systems involved in cognitive-emotional control and visual processing of negative stimuli. Furthermore, poorer self-reflectiveness may be associated with brain systems subserving control and execution.